EFFICACY AND TOLERABILITY OF FLUPIRTINE MALEATE VERSUS DICLOFENAC IN MECHANICAL LOW BACK PAIN – A PROSPECTIVE COMPARATIVE STUDY - R, RAMYA; S, RAJARAM; V, LEENA RANJINI; S, NATHIYA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Low back pain (LBW) is one of the most common reasons for adults visiting orthopedic outpatient clinics in our country. The objective of the study was to compare the safety and efficacy of flupirtine, a selective neuronal potassium channel opener, with diclofenac, a widely used NSAIDs analgesic, in patients with mechanical LBW (MLBP). Methods: This prospective, open-labeled, and randomized comparative clinical study included 100 patients with MLBP for more than 6 weeks. Fifty patients received flupirtine 100 mg, and 50 patients received diclofenac 100 mg for 7 days. Follow-up was done on day 8 and day 30. Assessments of functional improvement by the Oswestry Disability Index (ODI), pain relief by the Visual Analog Scale (VAS), Numerical Rating Scale (NRS), and Pain Relief Rate (PRR) were recorded. Safety and tolerability were also assessed. Data were analyzed using the Chi-square and Paired student t-tests. Results: VAS, NRS, and ODI scores were assessed for each visit (0, 1, and 2), and PRR was assessed on visits 1 and 2. VAS (p<0.05), NRS (p<0.05) scores, and sustained effect after stoppage of the drug were found to be better in the flupirtine group compared to the diclofenac group. Flupirtine was well tolerated. More patients reported adverse events in diclofenac than in the flupirtine group. Conclusion: Flupirtine may have a superior sustained effect compared to diclofenac in MLBP.